1991
DOI: 10.1038/jcbfm.1991.108
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis-Induced Ischemic Brain Damage: Are Free Radicals Involved?

Abstract: Summary: Substantial evidence exists that reactive oxy gen species participate in the pathogenesis of brain dam age following both sustained and transient cerebral isch emia, adversely affecting the vascular endothelium and contributing to the formation of edema. One likely trig gering event for free radical damage is delocalization of protein-bound iron. The binding capacity for some iron binding proteins is highly pH sensitive and, consequently, the release of iron is enhanced by acidosis. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 59 publications
0
8
1
1
Order By: Relevance
“…Furthermore, the pH optimum of the hydroxyl radical producing reaction between iron and ascorbic acid is close to pH 6 (Almaas et al 1997). On the other hand, Lundgren et al found no evidence for acidosis-induced free radical formation during cerebral ischemia in vivo (Lundgren et al 1991). In the present study, acidosis (during both ischemia and reoxygenation) increased the formation of isoprostanes by 50%.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Furthermore, the pH optimum of the hydroxyl radical producing reaction between iron and ascorbic acid is close to pH 6 (Almaas et al 1997). On the other hand, Lundgren et al found no evidence for acidosis-induced free radical formation during cerebral ischemia in vivo (Lundgren et al 1991). In the present study, acidosis (during both ischemia and reoxygenation) increased the formation of isoprostanes by 50%.…”
Section: Discussioncontrasting
confidence: 77%
“…On the other hand, Lundgren et al . found no evidence for acidosis‐induced free radical formation during cerebral ischemia in vivo (Lundgren et al . 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The excitatory amino acids elevated cytosolic-free calcium (Ca 2ϩ ), and in pathological conditions, a Ca 2ϩ overload may occur, which can set off a cascade of events, such as phospholipase activation, potentially leading to free-radical production (3). The formation of oxygen-derived free radicals may occur in the electron transport chain, in metabolic processes such as free fatty acids, and in purine and nitric oxide (35)(36)(37)(38). These oxidants destroy or inactivate cellular and subcellular proteins and various enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged ischemia increases extracellular glutamate concentration enough to cause oxidative stress by excitotoxic mechanisms . However, brief ischemia without reoxygenation does not increase production of superoxide (Nelson et al 1992) or hydrogen peroxide (Lundgren et al 1991), and it initially diminishes formation of hydroxyl radical (Globus et al 1995). Reperfusion of the transiently ischemic region accelerates formation of the reactive oxygen species that cause mitochondrial dysfunction, DNA fragmentation, and cell death (Kuroda et al 1996;Murakami et al 1997).…”
Section: Antioxidants and Traumamentioning
confidence: 99%